Conversational Implicature Used in Warung Kopi Podcast on the Has Creative Youtube Channel - Aditama, Azmi Fahrezi (Universitas Harapan Medan, 2025)
This study aims to identify the types and meaning of conversational implicature used in warung kopi podcast. This research is a descriptive qualitative study which data is obtained from a warung kopi podcast conversation played by Praz Teguh and Mael Lee. This research uses Grice's (1975) theory of implicature to analyze the data. The data collection techniques in this research are observation method and note-taking method by Sudaryanto (2015). Based on the results of the analysis, 30 implied utterances were found in the Club Random podcast episode with Howie Mandel. Of the 30 utterances, 22 utterances are included in the particular implicature, and 8 utterances are included in the generalized conversational implicature. Particularized conversational implicature is more dominant in this study. With context, the meaning conveyed can differ from what is actually said.